Parks’ modified technique for treatment of upper and medium transphincteral fistula - Bermúdez, Jorge; Veirano, Gustavo (Cirugía del Uruguay, 1988)
The aim of Parks' technique is the preservation of ali the externa! sphincter. Crypt resection with a section of the interna! sphincter prevents relapses and the seton placed in the traject ensures drainage. In spite of this, in 20% of the cases, delayed sphincter section is necessary because of trajee! persistence. In a series of cases authors used Parks' technique but instead of placing Seton, the externa! muscular orifice was closed from the a·nal canal with Dexon 4-0 stitches. Results were optimum from the point of view of trajects' primary healing (1-2 weeks), rather slower for the interna! defect (3-5 weeks) with no subsequent incontinence sequel. No relapses were found in follow-ups of 4 months up to 5 years.